Analyzing the Level of Anxiety Disorders of Final-Year Students by Applying the Fuzzy Mamdani Method - Virdyra Tasril; Muhammad Iqbal; Febby Madonna Yuma (Jurnal Riset Informatika, 2023)
Anxiety disorders are included in mental health disorders that are more or less experienced by society. The focus of this study was samples of final-year students who felt this disorder both psychologically and psychologically. Disorders often experienced by the average panic disorder worry from thesis guidance to conducting the final trial due to student unpreparedness and lack of confidence. The purpose of this study is to obtain the results of an analysis of the results of the diagnosis of anxiety disorders in final-year students. The indicators used are three variables, physical, cognitive, and behavioral, each with its symptoms. The fuzzy Mamdani method is used with the help of Matlab software to analyze the results. Based on five samples of students with anxiety disorders experienced by final-year students aged 20-22, the largest was in cognitive disorders, and the lowest was in behavioral variables.